Psychotherapeutische Sprechstunde am Arbeitsplatz: Zusammenhänge zwischen Unternehmensgröße und psychosomatischer Gesundheit - Hander, Nicole R.; Krohn, Julia; Kohl, Fiona; Heming, Meike; Erim, Yesim; Herold, Regina; Kröger, Christoph; Hansmann, Marieke; Köllner, Volker; Chrysanthou, Sophia; Wegewitz, Uta; Schröder, Ute B.; et al. (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2024)
Background: The utilization of psychotherapeutic consultation at work (PT-A) has so far been investigated in large enterprises (LEs). These differ structurally from small(est) and medium-sized enterprises (SMEs). Differences in the user profiles of a PT‑A with regard to psychosomatic health, work-related self-efficacy, and work ability depending on company size have hardly been investigated. This study also examined differences in the employees’ perception of the psychosocial safety climate (PSC) in the company, which represents management’s efforts to promote mental health. Methods: As part of the Early Intervention in the Workplace intervention study called “friaa”, employees from LEs and SMEs interested in a PT‑A were surveyed throughout Germany from September 2021 to January 2023. Using t‑ and χ2-tests, differences between employees in LEs (n = 439) and SMEs (n = 109) were examined with regard to the ICD-10 F diagnostic code (“International Statistical Classification of Diseases and Related Health Problems”; mental and behavioral disorders), depression (PHQ-9), anxiety (GAD-2), level of functioning (GAF), somatic symptom burden (SSS-8), health (VR-12), ability to work (WAI), self-efficacy (SOSES), and psychosocial safety climate (PSC-4). The association between these variables and especially the PSC‑4 were investigated using correlation analysis. Results: Both groups showed similar levels of stress. From the employees’ perspective, psychosocial issues were addressed significantly more frequently in LEs than in SMEs with a medium effect size. The study provided initial indications that in LEs there were positive correlations of the PSC‑4 with SOSES and WAI and negative ones with PHQ‑9 and SSS‑8. Discussion: The comparable psychological strain on employees in LEs and SMEs points to the need for behavioral and structural preventive measures regardless of the company size. Mainly in SMEs, organizational communication of psychosocial health should be given greater priority.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Early diagnosis and prevention; Mental health; Psychosocial safety climate; SME; Workplace health promotion